Flame-retardant eutectic polymer electrolyte based on in-situ polymerization, preparation method and solid-state lithium battery

By using in-situ polymerization technology to prepare flame retardant eutectic polymer electrolytes in lithium-ion batteries, the high-voltage instability of liquid electrolytes and uncontrollable growth of lithium dendrites in lithium-ion batteries are solved, and high safety, high energy density and good cycling performance are achieved.

CN119650835APending Publication Date: 2025-03-18XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411862368.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the high-voltage instability of liquid electrolytes and the uncontrollable growth of lithium dendrites lead to insufficient energy density and safety, especially in high voltage and lithium metal anode applications.

Method used

The flame-retardant eutectic polymer electrolyte based on in situ polymerization is used, and the monomers of hydrogen bond acceptor and hydrogen bond donor are mixed in an inert gas atmosphere, and functional additives, ester polymer monomers and initiators are added to carry out in situ radical polymerization reaction to form an eutectic polymer electrolyte with high ionic conductivity and flame retardant properties.

Benefits of technology

It realizes high safety, high energy density and good interface contact of lithium-ion batteries, inhibits the growth of lithium dendrites, reduces side reactions and corrosion problems, and improves the cycle stability and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650835A_ABST
    Figure CN119650835A_ABST
Patent Text Reader

Abstract

The invention discloses a flame-retardant eutectic polymer electrolyte based on in-situ polymerization, a preparation method and a solid-state lithium battery, and belongs to the technical field of lithium battery polymer electrolytes.The preparation method comprises the following steps that in the inert gas atmosphere, an amide hydrogen bond donor and alkali metal salt are evenly mixed, and a mixture is obtained; the eutectic electrolyte is obtained by utilizing the interaction of Li-N and Li-O; adding a functional additive, an ester polymer monomer and an initiator into the eutectic electrolyte, and uniformly mixing to obtain a precursor solution; and injecting the precursor solution into a diaphragm in a lithium ion battery to be assembled, sealing, and performing in-situ free radical polymerization reaction to form the flame-retardant eutectic polymer electrolyte, thereby obtaining the solid-state lithium battery of the flame-retardant eutectic polymer electrolyte based on in-situ polymerization. The eutectic polymer electrolyte disclosed by the invention has a flame-retardant property, the safety of the lithium battery is greatly improved, meanwhile, the eutectic polymer electrolyte has high ionic conductivity, the rate capability of the battery is improved, and stable long circulation of the assembled solid-state lithium battery is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium battery polymer electrolytes and relates to a flame retardant eutectic polymer electrolyte based on in-situ polymerization, a preparation method and a solid-state lithium battery. Background Art

[0002] In the past few decades, significant advances in lithium-ion battery technology have driven the revolution of portable electronic products and have been successfully applied to electric vehicles on a large scale. In order to meet the needs of future applications, the next generation of batteries must have advantages such as high energy density, high safety, and low cost-effectiveness. In particular, the energy density of batteries used in new energy vehicles must be greater than 500Wh kg. -1 . In general, energy density can be increased by increasing the battery voltage range. Currently, research efforts focus on increasing the battery operating voltage to improve energy density, which poses a major challenge because this strategy may lead to premature capacity loss. This is caused by the high-voltage instability of organic carbonate-based solvents used in standard liquid electrolytes (>4.3V vs Li / Li + In addition, lithium metal has a high theoretical specific capacity (3861 mAh g -1 ), low density and extremely low electrode potential, making it an ideal anode material. Unfortunately, the uncontrollable lithium dendrites caused by the non-uniform deposition of lithium during the cycle of lithium metal seriously affect the application of lithium metal anodes, and the commercial flammable liquid electrolyte system has serious safety hazards such as fire and explosion when used in lithium metal systems. Therefore, using solid electrolytes to replace traditional organic electrolytes is an effective way to improve battery safety and energy density.

[0003] Polymer electrolytes have attracted extensive attention due to their safety, processability, energy density and high compatibility with lithium metal anodes. Using polymer electrolytes to cope with the uncontrollable growth and evolving relative volume changes of lithium dendrites in lithium metal batteries and the lack of a matching safe electrolyte system is the optimal solution for developing the next generation of high-energy batteries.

[0004] Common methods for preparing polymer electrolytes include physical polymerization, chemical cross-linking, and polymer matrix polymerization, which can be divided into two categories: non-in-situ preparation and in-situ preparation. Non-in-situ preparation refers to the process obtained before the battery assembly process, mostly in the form of independent membranes. The preparation methods of non-in-situ polymer electrolytes mainly include phase inversion, solution casting, and electrospinning. Polymer electrolytes prepared non-in-situ cannot fully penetrate into the pores of the electrode material, resulting in poor interface contact and high interface impedance. In addition, the above-mentioned non-in-situ methods are always accompanied by the volatilization of a large amount of organic solvents, which is harmful to the environment. Therefore, in-situ polymer electrolytes are proposed to solve the problem of electrolyte / electrode interface contact. Usually, a liquid electrolyte precursor is injected into the battery and gradually transformed into a quasi-solid polymer state under specific conditions to solve the interface problem. Summary of the invention

[0005] In view of the problems in the prior art, the purpose of the present invention is to provide a flame retardant eutectic polymer electrolyte based on in-situ polymerization, a preparation method and a solid-state lithium battery. The eutectic polymer electrolyte formed in this method has high ionic conductivity, high safety, a wide electrochemical window and cycle stability, so that the lithium-ion battery can maintain good interface contact and cycle stability.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization comprises the following steps:

[0008] In an inert gas atmosphere, a monomer having a hydrogen bond acceptor and a monomer having a hydrogen bond donor are uniformly mixed to obtain a eutectic electrolyte;

[0009] Adding functional additives, ester polymer monomers and initiators into the eutectic electrolyte, and mixing them evenly to obtain a precursor solution;

[0010] The precursor solution is subjected to an in-situ free radical polymerization reaction to form a solid-state lithium battery with a flame-retardant eutectic polymer electrolyte.

[0011] Further, the hydrogen bond donor is one of trifluoroacetamide, N-methylacetamide, N-dimethylacetamide, isopropylacrylamide, N-ethylacetamide and N-diethylformamide;

[0012] The hydrogen bond acceptor is one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium trifluoromethanesulfonate and lithium bis(difluorosulfonyl)imide.

[0013] The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1-1:10.

[0014] Furthermore, the mass fraction of the functional additive in the precursor solution is 1wt%-20wt%, the mass fraction of the ester polymer monomer in the precursor solution is 2wt%-10wt%, and the mass fraction of the initiator in the precursor solution is 0.1wt%-2wt%.

[0015] Further, the functional additive is at least one of fluoroethylene carbonate, vinylene carbonate, lithium nitrate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, tris(pentafluorophenyl)borane, triphenylphosphine oxide and 1,3-propylene sultone;

[0016] Monofunctional acrylate and methacrylate monomers and difunctional acrylate and methacrylate monomers;

[0017] Initiators include thermal initiators and photoinitiators.

[0018] Further, the monofunctional acrylate or methacrylate monomer is one of tetraethylene glycol diacrylate, polyethylene glycol diacrylate, poly(diethylene glycol carbonate), dimethacrylate, tripropylene glycol diacrylate, ethylene glycol dimethacrylate, poly(ethylene glycol) dimethacrylate, 1,6-hexanediol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate and 1,3-butanediol diacrylate;

[0019] The difunctional acrylate and methacrylate monomer is one of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate and pentaerythritol tetraacrylate;

[0020] The diaphragm is one of PP2500 type, PP2325 type, GF / A glass fiber diaphragm and GF / C glass fiber diaphragm.

[0021] Further, the thermal initiator is one of azobisisobutyronitrile and methylenebisacrylamide;

[0022] The photoinitiator was 2-hydroxy-2-methyl-1-phenylpropanone.

[0023] Furthermore, the in-situ free radical polymerization reaction includes thermal polymerization and ultraviolet polymerization.

[0024] Furthermore, the conditions for thermal polymerization are 60° C.-80° C., and the holding time is 15-720 min; the conditions for ultraviolet polymerization are wavelength 200-380 nm, and the irradiation time is 10-60 min.

[0025] A flame-retardant eutectic polymer electrolyte based on in-situ polymerization.

[0026] A solid-state lithium battery comprises a positive electrode, a negative electrode and a flame-retardant eutectic polymer electrolyte based on in-situ polymerization as claimed in claim 9 between the positive electrode and the negative electrode.

[0027] Furthermore, the positive electrode includes any one of lithium iron phosphate, lithium cobalt oxide, lithium iron manganese phosphate, lithium vanadium fluorophosphate, NCM622 type positive electrode material, NCM811 type positive electrode material and NCM9 type positive electrode material, and the negative electrode is any one of lithium metal sheet, lithium indium alloy, lithium titanate, silicon negative electrode and silicon carbon negative electrode.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The flame-retardant eutectic polymer electrolyte obtained by the in-situ polymerization strategy of the present invention can effectively improve the interfacial compatibility, and the tough polymer network can inhibit the growth of lithium dendrites. The eutectic electrolyte formed by intermolecular forces is used as the matrix of the electrolyte, which has an intrinsic flame retardant effect, solves the safety problem of lithium batteries from the source, and does not produce by-products during the synthesis of the eutectic electrolyte, so it is both environmentally friendly and economical and efficient. The flame-retardant eutectic polymer electrolyte is obtained by simple free radical polymerization, and has the advantages of high ionic conductivity and wide electrochemical window. In the present invention, due to the strong complexation between ions in the monomers with hydrogen bond acceptors and hydrogen bond donors, the hydrolysis of acidic groups is effectively alleviated, thereby reducing the generation of corrosive hydrofluoric acid. In addition, the positive electrode electrolyte interface layer is optimized by using functional additives, which slows down the structural degradation of the high nickel positive electrode and the dissolution of transition metals. The present invention introduces functional additives into the precursor solution, adjusts the solvation structure of lithium ions, obtains a eutectic polymer electrolyte with fast lithium ion transmission number through functional customization, inhibits the side reaction between the eutectic electrolyte and lithium metal, slows down the corrosion of the eutectic electrolyte to the positive and negative electrodes, realizes uniform deposition of lithium ions, and expands the application range of the eutectic electrolyte in lithium batteries. The in-situ polymerized flame-retardant eutectic polymer electrolyte of the present invention can be assembled into a solid-state lithium-ion battery, and after assembly in practice, a series of electrochemical tests show good cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A flow chart of a method for preparing an in-situ polymerized flame-retardant eutectic polymer electrolyte provided by the present invention;

[0031] Figure 2 The flame retardant eutectic polymer electrolyte precursor solution and the flame retardant eutectic polymer electrolyte prepared according to Example 1 of the present invention; wherein (a) is the precursor solution, and (b) is the flame retardant eutectic polymer electrolyte;

[0032] Figure 3This is a graph of the ionic conductivity of the flame retardant eutectic polymer electrolyte prepared according to Example 1 of the present invention;

[0033] Figure 4 for Figure 3 A partial enlarged view of the

[0034] Figure 5 The electrochemical window diagram of the flame retardant eutectic polymer electrolyte prepared according to Example 1 and Comparative Example 1 of the present invention;

[0035] Figure 6 The safety performance test diagram of the flame retardant eutectic polymer electrolyte prepared according to Example 3 of the present invention, wherein (a) is a direct ignition test diagram, and (b) is a thermogravimetric diagram;

[0036] Figure 7 This is a test result diagram of a flame retardant eutectic polymer electrolyte prepared according to Example 5 of the present invention used in a lithium metal symmetric battery;

[0037] Figure 8 The cycle performance and coulomb efficiency diagram of the solid-state lithium battery prepared according to Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0038] Fig. 9 This is a rate performance diagram of a solid-state lithium battery prepared according to Example 1 of the present invention;

[0039] Fig.10 is the interface impedance of the corresponding batteries in Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0040] In order to make the above-mentioned purpose, performance characteristics and preparation method of the present invention clearer and easier to understand, the present invention is further described in conjunction with the following examples. The examples are preferred in the experimental process and are only used to more completely illustrate the present invention, but cannot be understood as limiting the scope of application of the present invention.

[0041] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more obvious and easier to understand, the technical solutions in the embodiments of the present invention will be clearly described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0042] Eutectic solvents are green liquid media, which are a mixture of two or three components that self-associate through hydrogen bonding interactions. Eutectic solvents have many common properties with ionic liquids, such as low vapor pressure, good thermal and chemical stability, and non-flammability. Due to the instability and volatility of organic liquid electrolytes, they are inherently non-flammable. Based on this, the present invention uses eutectic solvents as safe electrolytes for energy storage devices, especially lithium batteries.

[0043] See also Figure 1The present invention provides a method for preparing a solid-state lithium battery based on an in-situ polymerized flame-retardant eutectic polymer electrolyte, comprising the following steps:

[0044] (1) In an inert gas atmosphere, two monomers having a hydrogen bond acceptor and a hydrogen bond donor are stirred and mixed under specific conditions to obtain a uniform and transparent eutectic electrolyte;

[0045] (2) introducing functional additives, ester polymer monomers and initiators into the eutectic electrolyte, and stirring and mixing under specific conditions to obtain a precursor solution;

[0046] (3) Injecting the obtained precursor solution into the separator of the lithium-ion battery to be assembled, and using a sealing machine to complete the sealing. The in-situ polymerized flame-retardant eutectic polymer electrolyte is obtained by in-situ free radical polymerization and applied to solid-state lithium batteries.

[0047] Preferably, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1-1:10, the mass fraction of the functional additive in the precursor solution is 1wt%-20wt%, the mass fraction of the ester polymer monomer in the precursor solution is 2wt%-10wt%, the mass fraction of the initiator in the precursor solution is 0.1wt%-2wt%, the stirring temperature is 25-80°C, the time is 20-360min, and the diaphragm is one of PP2500 type, PP2325 type, GF / A glass fiber diaphragm and GF / C glass fiber diaphragm.

[0048] In the above technical scheme, the hydrogen bond donor in step (1) is an amide solid, including one of trifluoroacetamide, N-methylacetamide, N-dimethylacetamide, isopropylacrylamide, N-ethylacetamide and N-diethylformamide; the hydrogen bond acceptor is a metal salt, specifically including one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium borooxalate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate and lithium bis(difluorosulfonyl)imide.

[0049] In the above technical solution, the functional additive in step (2) includes at least one of fluoroethylene carbonate, vinylene carbonate, lithium nitrate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, tris(pentafluorophenyl)borane, triphenylphosphine oxide, and 1,3-propylene sultone.

[0050] Furthermore, the ester polymer monomers in step (2) include: mono / difunctional acrylate and methacrylate monomers, and the monofunctional acrylate and methacrylate monomers include: one of tetraethylene glycol diacrylate, polyethylene glycol diacrylate, poly(diethylene glycol carbonate), dimethacrylate, tripropylene glycol diacrylate, ethylene glycol dimethacrylate, poly(ethylene glycol) dimethacrylate, 1,6-hexanediol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate and 1,3-butylene glycol diacrylate. The difunctional acrylate and methacrylate monomers include: one of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate and pentaerythritol tetraacrylate.

[0051] Furthermore, the initiator in step (2) includes two forms: a thermal initiator and a photoinitiator, wherein the thermal initiator is one of azobisisobutyronitrile and methylenebisacrylamide, and the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone.

[0052] Furthermore, the in-situ free radical polymerization reaction in step (3) includes thermal polymerization and ultraviolet polymerization, wherein the thermal polymerization condition is 60°C-80°C and the holding time is 15-720min; the ultraviolet polymerization condition is 200-380nm in wavelength and the irradiation time is 10-60min.

[0053] The reaction formula for obtaining a flame retardant eutectic polymer electrolyte by thermal free radical polymerization is as follows:

[0054]

[0055] A further object of the present invention is to provide a solid-state lithium battery based on an in-situ polymerized flame-retardant eutectic polymer electrolyte, comprising a positive electrode, a polymer electrolyte, and a negative electrode, wherein the polymer electrolyte is obtained by the preparation method of the flame-retardant eutectic polymer electrolyte.

[0056] Furthermore, the positive electrode includes any one of lithium iron phosphate, lithium cobalt oxide, lithium iron manganese phosphate, lithium vanadium fluorophosphate, NCM622 type positive electrode material, NCM811 type positive electrode material and NCM9 type positive electrode material, and the negative electrode is any one of lithium metal sheet, lithium indium alloy, lithium titanate, silicon negative electrode and silicon carbon negative electrode.

[0057] The scheme of the present invention is described in more detail below with reference to the embodiments.

[0058] Example 1

[0059] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium bis(trifluoromethanesulfonyl imide) and N-methylacetamide in a molar ratio of 1:4 are stirred at 60° C. for 60 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0060] (2) Preparing a precursor solution: adding fluoroethylene carbonate and lithium nitrate as functional additives, ethoxylated trimethylolpropane triacrylate as an ester polymer monomer, and azobisisobutyronitrile as a thermal initiator to the above eutectic electrolyte, stirring at 25° C. for 60 min until the mixture is uniformly mixed to obtain a precursor solution for standby use; wherein the concentration of fluoroethylene carbonate is 10 wt %, the concentration of lithium nitrate is 2 wt %, the concentration of ethoxylated trimethylolpropane triacrylate is 2 wt %, and the concentration of azobisisobutyronitrile is 0.1 wt %.

[0061] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries are used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode uses lithium iron phosphate, and the separator uses glass fiber separator GF / A. The above precursor solution is injected into the separator, and then assembled with the lithium metal negative electrode and the negative electrode shell to obtain a button-type lithium-ion battery, and then the button-type solid-state lithium-ion battery is obtained by in-situ polymerization at 60°C for 720 minutes.

[0062] Example 2

[0063] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium bis(trifluoromethanesulfonyl imide) and trifluoroacetamide in a molar ratio of 1:6 are stirred at 50° C. for 120 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0064] (2) Preparing a precursor solution: adding lithium nitrate as a functional additive, polyethylene glycol diacrylate as an ester polymer monomer, and azobisisobutyronitrile as a thermal initiator to the above eutectic electrolyte, stirring at 25°C for 120 minutes until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of lithium nitrate is 3wt%, the concentration of polyethylene glycol diacrylate is 10wt%, and the concentration of azobisisobutyronitrile is 0.2wt%.

[0065] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries were used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode used NCM811, and the separator used glass fiber separator GF / A. The above precursor solution was injected into the separator, and then assembled with the lithium metal negative electrode and the negative electrode shell to obtain a button-type lithium-ion battery, and then the button-type solid-state lithium-ion battery was obtained by in-situ polymerization at 70°C for 15 minutes.

[0066] Example 3

[0067] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium trifluoromethanesulfonate and N-diethylformamide in a molar ratio of 1:10 are stirred at 50° C. for 30 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0068] (2) Preparing a precursor solution: adding fluoroethylene carbonate and tris(trimethylsilyl)phosphate as functional additives, pentaerythritol tetraacrylate as an ester polymer monomer, and azobisisobutyronitrile as a thermal initiator to the above eutectic electrolyte, stirring at 25°C for 120 minutes until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of fluoroethylene carbonate is 10wt%, the concentration of tris(trimethylsilyl)phosphate is 2wt%, the concentration of pentaerythritol tetraacrylate is 2wt%, and the concentration of azobisisobutyronitrile is 0.5wt%.

[0069] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries are used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode uses lithium vanadium fluoride phosphate, and the separator uses glass fiber separator GF / A. The above precursor solution is injected into the separator, and then assembled with the silicon negative electrode and the negative electrode shell to obtain a button-type lithium-ion battery, and then the button-type solid-state lithium-ion battery is obtained by in-situ polymerization at 65°C for 360 minutes.

[0070] Example 4

[0071] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium hexafluorophosphate and isopropyl acrylamide in a molar ratio of 1:6 are stirred at 55° C. for 60 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0072] (2) Preparing a precursor solution: adding lithium nitrate and tri(pentafluorophenyl)borane as functional additives, pentaerythritol tetraacrylate as an ester polymer monomer, and 2-hydroxy-2-methyl-1-phenylacetone as an ultraviolet light initiator to the above eutectic electrolyte, stirring at 25° C. for 100 min until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of lithium nitrate is 2 wt %, the concentration of tri(pentafluorophenyl)borane is 2 wt %, the concentration of pentaerythritol tetraacrylate is 2 wt %, and the concentration of 2-hydroxy-2-methyl-1-phenylacetone is 2 wt %.

[0073] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries were used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode used lithium cobalt oxide and the separator used PP2500. The above precursor solution was injected into the separator, and then in-situ polymerization was completed by irradiation under 365nm ultraviolet light for 20 minutes, and then assembled with the silicon-carbon negative electrode and the negative electrode shell to obtain a button-type solid-state lithium-ion battery.

[0074] Example 5

[0075] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium bis(difluorosulfonyl)imide and N-dimethylacetamide in a molar ratio of 1:7 are stirred at 50° C. for 60 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0076] (2) Preparing a precursor solution: adding vinylene carbonate as a functional additive, ethylene glycol dimethacrylate as an ester polymer monomer, and azobisisobutyronitrile as a thermal initiator to the above eutectic electrolyte, stirring at 25° C. for 120 min until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of vinylene carbonate is 10 wt %, the concentration of ethylene glycol dimethacrylate is 10 wt %, and the concentration of azobisisobutyronitrile is 1 wt %.

[0077] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries are used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode uses NCM622, and the separator uses glass fiber separator GF / A. The above precursor solution is injected into the separator, and then assembled with the lithium metal negative electrode and the negative electrode shell to obtain a button-type lithium-ion battery, and then the button-type solid-state lithium-ion battery is obtained by in-situ polymerization at 75°C for 15 minutes.

[0078] Example 6

[0079] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium difluorooxalatoborate and N-ethylacetamide in a molar ratio of 1:10 are stirred at 70° C. for 240 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0080] (2) Preparing a precursor solution: adding tri(trimethylsilyl)borate and 1,3-propylene sultone as functional additives, poly(ethylene glycol) dimethacrylate as an ester polymer monomer, and 2-hydroxy-2-methyl-1-phenylpropanone as an ultraviolet light initiator to the above eutectic electrolyte, stirring at 25° C. for 360 min until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of tri(trimethylsilyl)borate is 2 wt %, the concentration of 1,3-propylene sultone is 2 wt %, the concentration of poly(ethylene glycol) dimethacrylate is 3 wt %, and the concentration of 2-hydroxy-2-methyl-1-phenylpropanone is 1.5 wt %.

[0081] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries were used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode used lithium iron manganese phosphate and the separator used PP2500. The above precursor solution was injected into the separator, and then in-situ polymerization was completed by irradiation under 365nm ultraviolet light for 60 minutes, and then assembled with lithium indium alloy negative electrode and negative electrode shell to obtain a button-type solid-state lithium-ion battery.

[0082] Example 7

[0083] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium tetrafluoroborate and N-ethylacetamide in a molar ratio of 1:10 are stirred at 80° C. for 20 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0084] (2) Preparing a precursor solution: adding triphenylphosphine oxide and 1,3-propylene sultone as functional additives, tripropylene glycol diacrylate as an ester polymer monomer, and 2-hydroxy-2-methyl-1-phenylpropanone as an ultraviolet light initiator to the above eutectic electrolyte, stirring at 25° C. for 360 min until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of triphenylphosphine oxide is 1 wt %, the concentration of 1,3-propylene sultone is 5 wt %, the concentration of tripropylene glycol diacrylate is 5 wt %, and the concentration of 2-hydroxy-2-methyl-1-phenylpropanone is 0.1 wt %.

[0085] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries are used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode uses lithium iron manganese phosphate and the separator uses PP2500. The above precursor solution is injected into the separator, and then in-situ polymerization is completed by irradiating it under ultraviolet light of 200-380nm for 10 minutes, and then assembled with lithium indium alloy negative electrode and negative electrode shell to obtain a button-type solid-state lithium-ion battery.

[0086] Example 8

[0087] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium perchlorate and N-ethylacetamide in a molar ratio of 1:3 are stirred at 25° C. for 360 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0088] (2) Preparing a precursor solution: adding tri(trimethylsilyl)borate as a functional additive, poly(diethylene glycol carbonate) as an ester polymer monomer, and 2-hydroxy-2-methyl-1-phenylacetone as an ultraviolet light initiator to the above eutectic electrolyte, stirring at 25° C. for 360 min until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of tri(trimethylsilyl)borate is 20 wt %, the concentration of 1,3-propylene sultone is 8 wt %, and the concentration of poly(diethylene glycol carbonate) is 1 wt %.

[0089] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries are used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode uses lithium iron manganese phosphate and the separator uses PP2500. The above precursor solution is injected into the separator, and then in-situ polymerization is completed by irradiating it under ultraviolet light of 200-380nm for 10 minutes, and then assembled with lithium indium alloy negative electrode and negative electrode shell to obtain a button-type solid-state lithium-ion battery.

[0090] Example 9

[0091] (1) preparing a eutectic electrolyte: in an argon environment in a glove box where the water and oxygen content is less than 0.01 ppm, lithium borooxalate and N-ethylacetamide in a molar ratio of 1:9 are stirred at 40° C. for 160 min until the mixture is uniformly mixed, and a uniform and transparent eutectic electrolyte is obtained after cooling;

[0092] (2) Preparing a precursor solution: adding vinylene carbonate as a functional additive, tetraethylene glycol diacrylate as an ester polymer monomer, and methylene bisacrylamide as a thermal initiator to the above eutectic electrolyte, stirring at 65° C. for 260 min until the mixture is uniformly mixed to obtain a precursor solution for standby use; the concentration of vinylene carbonate is 15 wt %, the concentration of tetraethylene glycol diacrylate is 4 wt %, and the concentration of methylene bisacrylamide is 1.5 wt %.

[0093] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries are used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode uses NCM622, and the separator uses glass fiber separator GF / A. The above precursor solution is injected into the separator, and then assembled with the lithium metal negative electrode and the negative electrode shell to obtain a button-type lithium-ion battery, and then the button-type solid-state lithium-ion battery is obtained by in-situ polymerization at 80°C for 20 minutes.

[0094] Comparative Example 1

[0095] The difference between Comparative Example 1 and Example 1 is that 10 wt % of fluoroethylene carbonate and 2 wt % of lithium nitrate are not added as functional additives. The specific steps are as follows:

[0096] (1) according to the preparation method of Example 1;

[0097] (2) Preparing a precursor solution: Add 2 wt % of ethoxylated trimethylolpropane triacrylate as an ester polymer monomer and 0.1 wt % of azobisisobutyronitrile as a thermal initiator to the above eutectic electrolyte, stir at 25° C. for 60 min until the mixture is uniformly mixed to obtain a precursor solution for standby use.

[0098] (3) According to the preparation method of Example 1.

[0099] The difference between this comparative example and Example 1 is that 10 wt% of fluoroethylene carbonate and 2 wt% of lithium nitrate are not added as functional additives, so the content of LiF and LiN3 generated in the solid electrolyte phase interface is relatively small. Figure 4 As shown, the electrochemical window of polymer electrolytes is narrow. Figure 7 This results in a low discharge specific capacity of the battery, and the capacity retention rate after 1000 cycles is lower than that of Example 1.

[0100] Comparative Example 2

[0101] The difference between Comparative Example 2 and Example 1 is that 2 wt % of ethoxylated trimethylolpropane triacrylate is not added as the ester polymer monomer and 0.1 wt % of azobisisobutyronitrile is not added, that is, the button cell is directly assembled as the liquid electrolyte. The specific steps are:

[0102] (1) Preparation of eutectic electrolyte: according to the preparation method of Example 1;

[0103] (2) preparing a precursor solution: adding 10 wt % of fluoroethylene carbonate and 2 wt % of lithium nitrate as functional additives to the above eutectic electrolyte, stirring at 25° C. for 60 min until the mixture is uniformly mixed, and obtaining a precursor solution for standby use;

[0104] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries are used and assembled in the order of positive electrode shell, positive electrode, separator, precursor solution, negative electrode, and negative electrode shell. Among them, the positive electrode uses lithium iron phosphate, and the separator uses glass fiber separator GF / A. The above precursor solution is injected into the separator, and then assembled with the lithium metal negative electrode and the negative electrode shell to obtain a button-type lithium-ion battery.

[0105] The difference between this comparative example and Example 1 is that 2 wt% of ethoxylated trimethylolpropane triacrylate as the ester polymer monomer and 0.1 wt% of azobisisobutyronitrile are not added, that is, the button cell is directly assembled as the liquid electrolyte. Figure 8 The battery corresponding to Comparative Example 2 shown loses capacity after 100 cycles.

[0106] Comparative Example 3

[0107] The difference between Comparative Example 3 and Example 1 is that the non-in-situ polymerization method is used for preparation, that is, the precursor solution is first prepared into a gel polymer and then the battery is packaged. The specific steps are:

[0108] (1) according to the preparation method of Example 1;

[0109] (2) according to the preparation method of Example 1;

[0110] (3) Assembly of button-type solid-state lithium-ion battery: CR2025 button batteries were used and assembled in the order of positive electrode shell, positive electrode, separator, gel polymer, negative electrode, and negative electrode shell. Among them, the positive electrode used lithium iron phosphate, and the separator used glass fiber separator GF / A. The above precursor solution was injected into the separator, and non-in-situ polymerization was completed by keeping it at 60°C for 720 minutes, and then assembled with lithium metal negative electrode and negative electrode shell to obtain a button-type lithium-ion battery.

[0111] The difference between this comparative example and Example 1 is that the non-in-situ polymerization method is used for preparation, that is, the precursor solution is first prepared into a gel polymer and then the battery is packaged. Fig. 9 The interfacial impedance of the battery corresponding to Comparative Example 3 is significantly greater than the interfacial impedance of the in-situ polymerization.

[0112] The test results of the above embodiments and comparative examples are shown in Table 1.

[0113] Table 1

[0114]

[0115]

[0116] It can be seen from Table 1 that Examples 1-6 using the solution provided by the present invention all have high room temperature ionic conductivity that can be used for practical applications. The room temperature ionic conductivity of the solution provided by Comparative Examples 1-3 is one order of magnitude lower than that of the embodiments provided by the present invention. In the charge and discharge tests, the discharge specific capacity, first cycle coulomb efficiency, cycle stability and interface compatibility of Examples 1-6 are significantly better than those of the comparative examples.

[0117] Figure 2 The physical picture and SEM picture of the flame retardant eutectic polymer electrolyte prepared according to Example 1 of the present invention are shown in FIG. As can be seen from the physical picture, the flame retardant eutectic polymer electrolyte prepared in Example 1 has a stable structure and no fluidity.

[0118] Figure 3 and Figure 4 The ionic conductivity diagram and the local magnified diagram of the flame retardant eutectic polymer electrolyte prepared according to Example 1 of the present invention are 2.67×10 -3 S cm -1 .

[0119] Figure 5 Graphs showing the electrochemical windows of the flame retardant eutectic polymer electrolytes prepared according to Example 1 and Comparative Example 1 of the present invention, wherein the electrochemical window of the flame retardant eutectic polymer electrolyte prepared in Example 1 is as high as 4.79V, while the electrochemical window of the electrolyte prepared in Comparative Example 1 is 4.2V.

[0120] Figure 6 The safety performance test diagram of the flame retardant eutectic polymer electrolyte prepared according to Example 3 of the present invention, wherein (a) is a thermogravimetric diagram and (b) is a direct ignition test diagram. The direct ignition experiment found that the flame retardant eutectic polymer electrolyte could not be ignited, and at a temperature as high as 151.5°C, there was basically no obvious weight loss phenomenon.

[0121] Figure 7 This is a test result diagram of the flame retardant eutectic polymer electrolyte prepared in Example 5 of the present invention for lithium metal symmetric batteries. -2 The lower symmetric lithium-ion battery maintains a stable overpotential during the 1000 h cycle.

[0122] Figure 8The cycle performance and coulomb efficiency diagrams of the solid-state lithium batteries prepared according to Example 1, Comparative Example 1 and Comparative Example 2 of the present invention show that after 1000 cycles at a rate of 0.5C, 80.4% of the discharge capacity and more than 99% of the coulomb efficiency can still be maintained. As shown in Comparative Example 1, the discharge specific capacity of the battery is low, and the capacity retention rate after 1000 cycles is lower than that of Example 1. The battery corresponding to Comparative Example 2 loses capacity after 100 cycles.

[0123] Fig. 9 The rate performance diagram of the solid-state lithium battery prepared according to Example 1 of the present invention can provide 155.3 mAh g at 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 4C, and 5C. -1 、150.7mAh g -1 , 140.2mAh g -1 、126.7mAh g -1 、108mAhg -1 , 93.4mAh g -1 、81.7mAh g -1 , 71.9mAh g -1 The discharge capacity.

[0124] Fig.10 : The interface impedance of the corresponding batteries of Example 1 and Comparative Example 3. It can be seen that the interface impedance of the solid-state battery prepared by in-situ polymerization in Example 1 is 145Ω, while the interface impedance of the non-in-situ polymerization solid-state battery in Comparative Example 3 is 440Ω.

[0125] The acrylic acid in the present invention may also be one of ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate and 1,3-butanediol diacrylate.

[0126] The present invention utilizes the interaction between Li-N and Li-O between amide hydrogen bond donors and alkali metal salts to form a eutectic electrolyte; then functional additives, ester polymer monomers and initiators are introduced into the eutectic electrolyte to obtain a precursor solution, which is injected into the battery to be assembled, and a eutectic polymer electrolyte with flame retardant properties is obtained by in-situ polymerization and applied to lithium batteries. The eutectic polymer electrolyte involved in the present invention has flame retardant properties, greatly improves the safety of lithium batteries, and has high ionic conductivity, improves battery rate performance, and the assembled solid-state lithium battery achieves stable long cycle.

[0127] The above embodiments are only embodiments with better effects in the present invention and cannot be understood as limiting the present invention. Any person skilled in the art can change, modify or replace the above methods without changing the technical solution and essence of the present invention.

Claims

1. A method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization, characterized in that: The following steps are involved: In an inert gas atmosphere, a monomer having a hydrogen bond acceptor and a monomer having a hydrogen bond donor are uniformly mixed to obtain a eutectic electrolyte; Adding functional additives, ester polymer monomers and initiators into the eutectic electrolyte, and mixing them evenly to obtain a precursor solution; The precursor solution is subjected to an in-situ free radical polymerization reaction to form a flame retardant eutectic polymer electrolyte based on in-situ polymerization.

2. The method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization according to claim 1, characterized in that: The hydrogen bond donor is one of trifluoroacetamide, N-methylacetamide, N-dimethylacetamide, isopropylacrylamide, N-ethylacetamide and N-diethylformamide; The hydrogen bond acceptor is one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium borodioxalate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate and lithium bis(difluorosulfonyl)imide; The molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:1-1:

10.

3. The method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization according to claim 1, characterized in that: The mass fraction of the functional additive in the precursor solution is 1wt%-20wt%, the mass fraction of the ester polymer monomer in the precursor solution is 2wt%-10wt%, and the mass fraction of the initiator in the precursor solution is 0.1wt%-2wt%.

4. The method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization according to claim 1, characterized in that: The functional additive is at least one of fluoroethylene carbonate, vinylene carbonate, lithium nitrate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, tris(pentafluorophenyl)borane, triphenylphosphine oxide and 1,3-propylene sultone; Monofunctional acrylate and methacrylate monomers and difunctional acrylate and methacrylate monomers; Initiators include thermal initiators and photoinitiators.

5. The method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization according to claim 4, characterized in that: The monofunctional acrylate or methacrylate monomer is one of tetraethylene glycol diacrylate, polyethylene glycol diacrylate, poly(diethylene glycol carbonate), dimethacrylate, tripropylene glycol diacrylate, ethylene glycol dimethacrylate, poly(ethylene glycol) dimethacrylate, 1,6-hexanediol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate and 1,3-butylene glycol diacrylate; The difunctional acrylate and methacrylate monomer is one of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate and pentaerythritol tetraacrylate; The diaphragm is one of PP2500 type, PP2325 type, GF / A glass fiber diaphragm and GF / C glass fiber diaphragm.

6. The method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization according to claim 5, characterized in that: The thermal initiator is one of azobisisobutyronitrile and methylenebisacrylamide; The photoinitiator was 2-hydroxy-2-methyl-1-phenylpropanone.

7. The method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization according to claim 1, characterized in that: In situ free radical polymerization reactions include thermal polymerization and UV polymerization.

8. The method for preparing a flame retardant eutectic polymer electrolyte based on in-situ polymerization according to claim 1, characterized in that: The conditions for thermal polymerization are 60° C.-80° C., and the holding time is 15-720 min. The conditions for ultraviolet polymerization are wavelength 200-380 nm, and the irradiation time is 10-60 min.

9. A flame retardant eutectic polymer electrolyte based on in-situ polymerization prepared according to the method according to any one of claims 1 to 8.

10. A solid-state lithium battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a flame retardant eutectic polymer electrolyte based on in-situ polymerization as claimed in claim 9 between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Eutectic solid electrolyte of lithium metal battery as well as preparation method and application of eutectic solid electrolyte

    CN117374383A

  • Preparation method of deep eutectic solvent-based polymer solid electrolyte for lithium battery

    CN117996178A

  • Ternary eutectic solid electrolyte, preparation method thereof and solid-state lithium battery

    CN119050455A

  • Electrolyte for lithium-sulphur batteries and lithium-sulphur batteries using the same

    US20060121355A1

  • Method of producing flame-resistant quasi-solid electrolytes and lithium batteries containing same

    US20220336859A1

Cited By

  • Preparation method of in-situ polymerization semi-solid electrolyte with gradient concentration distribution

    CN121460700A

  • All-solid-state polymer electrolyte for energy storage and frequency modulation of power grid and preparation method thereof

    CN122315082A